2005
DOI: 10.1093/molbev/msi099
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of RNA Secondary Structure Significantly Improves Likelihood-Based Estimates of Phylogeny: Examples from the Bilateria

Abstract: Sequences from ribosomal RNA (rRNA) genes have made a huge contribution to our current understanding of metazoan phylogeny and indeed the phylogeny of all of life. That said, some parts of this rRNA-based phylogeny remain unresolved. One approach to increase the resolution of these trees would be to use more appropriate models of sequence evolution in phylogenetic analysis. RNAs transcribed from rRNA genes have a complex secondary structure mediated by base pairing between sometimes distant regions of the rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 29 publications
4
93
0
2
Order By: Relevance
“…Second, the effect of selective pressures on parsimony analysis is loose (Van de Peer, 1993;Sloss et al, 2004). Finally, the down-weighting schemes of non-independent characters are too simplified and do not elucidate the different selective pressures in stem regions (Telford et al, 2005), and thus are not adequate for real data sets. Therefore, our results suggest that the down-weighting of characters of stems relative to loops might not be helpful to improve phylogenetic inference.…”
Section: Molecular Dynamics and Comparative Methods Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the effect of selective pressures on parsimony analysis is loose (Van de Peer, 1993;Sloss et al, 2004). Finally, the down-weighting schemes of non-independent characters are too simplified and do not elucidate the different selective pressures in stem regions (Telford et al, 2005), and thus are not adequate for real data sets. Therefore, our results suggest that the down-weighting of characters of stems relative to loops might not be helpful to improve phylogenetic inference.…”
Section: Molecular Dynamics and Comparative Methods Implicationsmentioning
confidence: 99%
“…Some recent analyses using the mitochondrial 16S rRNA gene, however, have depicted limited resolution of relationships within the Cyprinidae because of low nodal support (Gilles et al, 1998;Simons and Mayden, 1998;Simons et al, 2003;Li et al, 2005). It is well known that phylogenetic inferences depend not only on the appropriate choice of the marker, but also rely on comparative studies of the inherent phylogenetic contents of the molecular markers, such as base compositions, structural characteristics, parameter estimations and the adopted methods (Rosenberg and Kumar, 2003;Telford et al, 2005). One approach to improve the phylogenetic performance of the mitochondrial 16S rRNA gene is to incorporate information regarding the molecular structure of the marker in analyses for more accurate phylogenetic inference.…”
Section: Introductionmentioning
confidence: 99%
“…Separate evolution models for stem and loop regions of rRNA genes are preferable over a single evolution model for the entire sequence (Telford et al, 2005). We therefore divided sequences in stem and loop partitions based on published secondary structure models.…”
Section: Sequence Partitioning and Analysismentioning
confidence: 99%
“…The stem regions were analyzed under a doublet model with a single rate parameter and sixteen states (Schöninger and von Haeseler, 1994), representing all possible nucleotide pairings. Currently, the doublet model cannot be tested for goodness of Wt against other models with common software programs, such as Modeltest (Posada and Crandall, 1998) or MrModeltest (Nylander, 2004), but recent studies have shown that the 16-state doublet model signiWcantly outperformed simpler, 4-state, single-nucleotide models for stem regions of ribosomal sequences (Savill et al, 2001;Telford et al, 2005). No secondary structure information was used for the fragment of 28S rRNA because (1) no appropriate sipunculan reference sequence was available, and (2) only ca.…”
Section: Analysesmentioning
confidence: 99%
“…Better resolution and support for deep relationships was achieved by Telford et al (2005) who presented a phylogeny of the Bilateria, based on 72 complete 18S ribosomal RNA sequences. The sequences were analyzed under mixed models for the stem and loop regions of the ribosomal molecule, applying a doublet model that accounts for correlation of substitutions in the complementary stem regions.…”
Section: Introductionmentioning
confidence: 99%